THYRSOIDEA MACRURA (BLEEKER), THE LONGEST GIANT MORAY EEL FROM THE INDIAN WATERS - Bande, V N; Kartha, K N Rasachandra (Indian Journal of Fisheries, 2011)
A specimen of the giant moray eel, Thyrsoidea macrura, measuring 3080 mm in length (after preservation), obtained from Karwar is described. This appears to be the longest specimen of the species on record.